Analisis Karakteristik Mekanik pada Komposit Kertas Kardus yang Diperkuat dengan Serat Batang Pisang - Yusrizha Syahid; Rakhmad Arief Siregar; M. Yusuf Rahmansyah Siahaan (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2021)
The development of composite technology in the industrial world has progressed very rapidly until now. The most important element of composite materials is fiber, which gives the material characteristics such as strength, ductility and other mechanical properties. So far, cardboard and banana trees are only known as waste which is very easy to find in the housing environment. Therefore, research on composites was carried out by utilizing used cardboard and banana trees. The used cardboard then crushed and then mashed into a pulp them combined/mixed using kepok banana tree fiber and mas banana tress fiber which aims to determine the mechanical characteristics of the cardboard paper composite reinforced with materials. As the main adhesive while using PVac glue. The specimen mixture has variations of 30:70, 50:50 and 70:30 with each having 3 variabel in each composition, and the mixture of pulp with mixed kepok and mas fibers has a variation of 50:50 with 3 variabels, all using ASTM standart guidelines, 3039 M. The results of the tensile test of the highest fracture strain value was a mixture of pulp with banana kepok fiber at a composition of 30:70 of 0,0457 MPa, the highest value of yield strength was a mixture of pulp with mixed fiber composition of 50:50 of 1,125 MPa, The highest value of modulus of elasticity is the mixture of pulp and fiber mix 50:50 composition of 1,281 MPa.